PEMAKNAAN KOMUNIKASI BUDAYA MASYARAKAT SUNDA: (STUDY FENOMENOLOGI PEMAKNAAN KATA SAMPURASUN PADA REMAJA) - Deri Hudaya Deri; Haryadi Mujianto; Iis Zilfah Adnan; Gantha Pagarsandya (Commed : Jurnal Komunikasi dan Media, 2022)
The objective of this research is analyze the motives, meanings and experiences experienced by Garut youth in the use of the sentence "Sampurasun”. This study uses a qualitative phenomenological approach. Data collection techniques used by researchers are in-depth interviews, documentation, and observation. Data collection techniques used are in-depth interviews, documentation, and observation. With Sundanese Cultural Resource Person. The results of this study say that in Sundanese communication there is a characteristic in escorting conversations and what is used is a sentence "Sampurasun" which has a very deep meaning, but in its use today it experiences a shift in meaning which is influenced by internal and external factors in this case. The researcher found with various informants' perspectives on the motives of meaning and experience in the pronunciation of the sentence "Sampurasun" which resulted in an answer to several things that made a shift in the meaning of a sentence and also here found the actual meaning said by the resource person, namely the Sundanese Cultural himself.